Application research of municipal sludge treatment and disposal technology. Issue 1 (September 2020) - Zeng, Qian; Tang, Nvzhi; Chen, Hui; Xiao, Rui; Gong, Jinghui
Abstract: Municipal sludge treatment and disposal is an important problem that domestic and foreign sewage treatment production must face. To realize the effective treatment for municipal sludge disposal, in this paper, the properties of municipal sludge composition, introduces the present situation of disposal and analysis, as well as the treatment and disposal of municipal sludge technology and its application research is reviewed, providing reference for treatment and disposal of municipal sludge, in order to realize harmlessness, reduction and recycling of waste.